Anti-Allergic Rhinitis Effects of Medicinal Plants and Their Bioactive Metabolites via Suppression of the Immune System: A Mechanistic Review - Rahim, Nur Amira; Jantan, Ibrahim; Said, Mazlina Mohd; Jalil, Juriyati; Abd Razak, Amirul Faiz; Husain, Khairana (Frontiers in Pharmacology, 2021)
Allergic rhinitis (AR) is a common inflammatory condition of the nasal mucosa and it is an immunoglobulin E–mediated disease. The incidence and prevalence of AR globally have been escalating over recent years. Antihistamines, intranasal corticosteroids, decongestants, intranasal anticholinergics, intranasal cromolyn, leukotriene receptor antagonists and immunotherapy have been used in the treatment of AR. However, there is a need to search for more effective and safer remedies as many of the current treatments have reported side effects. Medicinal plants have been used traditionally to relief symptoms of AR but their efficacy and safety have not been scientifically proven. In this review, up-to-date reports of studies on the anti-allergic rhinitis of several medicinal plants and their bioactive metabolites through suppression of the immune system are compiled and critically analyzed. The plant samples were reported to suppress the productions of immunoglobulin E, cytokines and eosinophils and inhibit histamine release. The suppression of cytokines production was found to be the main mechanistic effect of the plants to give symptomatic relief. The prospect of these medicinal plants as sources of lead molecules for development of therapeutic agents to treat AR is highlighted. Several bioactive metabolites of the plants including shikonin, okicamelliaside, warifteine, methylwarifteine, luteolin-7-O-rutinoside, tussilagone, petasin, and mangiferin have been identified as potential candidates for development into anti-allergic rhinitis agents. The data collection was mainly from English language articles published in journals, or studies from EBSCOHOST, Medline and Ovid, Scopus, Springer, and Google Scholar databases from the year 1985 to 2020. The terms or keywords used to find relevant studies were allergic rhinitis OR pollinosis OR hay fever, AND medicinal plant OR single plant OR single herb OR phytotherapy. This comprehensive review serves as a useful resource for medicinal plants with anti-allergic rhinitis potential, understanding the underlying mechanisms of action and for future exploration to find natural product candidates in the development of novel anti-allergic rhinitis agents.